TECTONOPHYSICAL ZONING OF THE TIEN SHAN ACTIVE FAULTS – DETERMINISTIC STRONG EARTHQUAKE PREDICTION - K. E. Abdrakhmatov; O. M. Beloslyudtsev; A. V. Vilyaev; A. T. Danabaeva; T. L. Ibragimova; R. S. Ibragimov; V. A. Ismailov; A. Zh. Zhunusova; Z. А. Kalmetyeva; S. I. Kuzikov; A. V. Marinin; M. A. Mirzaev; et al. (Геодинамика и тектонофизика)
The January 23, 2024 М7.0 Wushi earthquake (China) put an end to the period of strong earthquake quiescence that had lasted for about 33 years in the Tien Shan. The risk of occurrence of new strong earthquakes in the coming years has been discussed among scientists. As a result of the conference on the basis of RS RAS in Bishkek in 2024, a team of the Russian, Kyrgyz, Kazakh and Uzbek seismologists, geophysicists and tectonophysicists has been formed to collaborate on a study of seismic prediction in the Tien Shan to reach a new level of understanding of this problem and to obtain the possibility to solve it. In the last few decades, a large Tien Shan earthquake database has been compiled and catalogued involving not only place, time and intensity of an event but also earthquake focal mechanisms. For the last years, M.V. Gzovsky laboratory of tectonophysics, IPE RAS, dealt with the development of new approaches which allow the stresses, extracted from the seismological database, to be recalculated into the Coulomb stresses on active faults. The recalculation experience showed that the fault zones with high Coulomb stresses can also be distinguished as more intensive seismic regime areas. Those are areas along which there is an occurrence of earthquakes, both moderate to strong and catastrophic (retrospective prediction for the 2008 Wenchuan and 2023 Pazarcik earthquakes). Thus, it becomes possible to perform tectonophysical zoning of faults which can be considered as a long-term earthquake prediction. The joint research program also involves a new level of development of approach to moderate-term earthquake prediction as applied to certain faults.